2004
DOI: 10.1128/jvi.78.12.6543-6555.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lyssavirus Matrix Protein Induces Apoptosis by a TRAIL-Dependent Mechanism Involving Caspase-8 Activation

Abstract: Lyssaviruses, which are members of the Rhabdoviridae family, induce apoptosis, which plays an important role in the neuropathogenesis of rabies. However, the mechanisms by which these viruses mediate neuronal apoptosis have not been elucidated. Here we demonstrate that the early induction of apoptosis in a model of lyssavirus-infected neuroblastoma cells involves a TRAIL-dependent pathway requiring the activation of caspase-8 but not of caspase-9 or caspase-10. The activation of caspase-8 results in the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 75 publications
1
66
0
1
Order By: Relevance
“…2D and E, we examined whether virion uncoating is required for the RV-induced expression of CXCL10 and CCL5 in microglia. BA1 is a selective and potent inhibitor of vacuolar H ϩ -ATPase, prevents endosomal acidification (13), and is applicable to the suppression of an acid-induced fusion of lyssaviral envelope with cell membrane (24). As shown in Fig.…”
Section: Infection Of Microglia By Rvmentioning
confidence: 99%
“…2D and E, we examined whether virion uncoating is required for the RV-induced expression of CXCL10 and CCL5 in microglia. BA1 is a selective and potent inhibitor of vacuolar H ϩ -ATPase, prevents endosomal acidification (13), and is applicable to the suppression of an acid-induced fusion of lyssaviral envelope with cell membrane (24). As shown in Fig.…”
Section: Infection Of Microglia By Rvmentioning
confidence: 99%
“…In addition, the M protein is involved in viral assembly and budding, and is associated with regulating the balance between viral transcription and replication [9,10,20]. Furthermore, the M protein acts as a major inducer of apoptosis in neuronal cells [23].However, although P and M proteins have been demonstrated to have several important functions in viral infection, these investigations have all been conducted using laboratory-adapted strains. In addition, few studies on P and M proteins in wild-type RV strains have been reported to date [30,31,32,33], and no reports have genetically characterized the P and M genes in Brazilian RV isolates.…”
mentioning
confidence: 99%
“…In addition, the M protein is involved in viral assembly and budding, and is associated with regulating the balance between viral transcription and replication [9,10,20]. Furthermore, the M protein acts as a major inducer of apoptosis in neuronal cells [23].…”
mentioning
confidence: 99%
“…However, the molecular basis of lyssavirus-induced neuronal apoptosis is still poorly understood (16,55). The involvement of the viral glycoprotein (G) in inducing neuronal apoptosis has been extensively shown (13,38,39,45), whereas we have suggested that M is an inducer of neuronal cell death through a tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-dependent pathway (29). However, the molecular mechanism of apoptosis has not been precisely defined, and little is known about mitochondrial involvement during lyssavirus infections (46).…”
mentioning
confidence: 99%